Principal Strategy in Improving Teacher Performance to Achieve Learning Effectiveness at Public Middle School in Banda Aceh City - Harun, Cut Zahri; Usman, Nasir; Chairi, Suci Natasya (Jurnal Pendidikan Progresif, 2020)
Principal Strategy in Improving Teacher Performance to Achieve Learning Effectiveness at Public Middle School in Banda Aceh City. Objectives: The aim of this research is to obtain complete and accurate data from the school about principal strategy in improving the learning effectiveness. Methods: This research used decriptive qualitative approach. The technique of data collection used are observation, interview, and documentation. The subject of this research are principals, and teachers. Findings: The result of this research shows that: (1) Principal strategy in the process of program arrangement are creating the team to arrange the program, to build disipline, to make employment contract, to motivate, to training and supervision; (2) The principal in implementing the coaching and development program to improve the learning effectiveness, the principal controlled the program implementation in order to be implemented well; (3) Principal strategy in evaluating the coaching and development program to improve the learning effectiveness is by doing evaluation. Keywords: Principal strategy, teacher performance, learning effectiveness. DOI: 10.23960/jpp.v10.i3.202011